Дослідження методів контолю послуг NB-IoT - Козубенко, B. C.; Сабурова, С. О. (ХНУРЕ, 2020)
Using the NB-IoT standard provides improved indoor coverage and the ability to serve many low-traffic devices, especially those that are not too sensitive to delays. Narrowband IoT is converted to low-cost chipsets and devices and very low power consumption of these devices, which ensures longlasting battery life